Geographical races of the honeybees (Apis Mellifera L.) of the Northern regions of Ethiopia - Mohammed, Nuru Adgaba (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2003)
The ideal climatic conditions and diversity of floral resources allow Ethiopia to sustain millions of honeybee colonies. Beekeeping is widely practiced and plays a significant role in the livelihood of the farming community of the country. Despite this, information on the types of geographical races of honeybees, their behavioural characters and the related ecological factors are not established. In this work an attempt was made to characterise the honeybee populations of the northern parts of Ethiopia based on the analyses of morphological, behavioural and ecological characteristics. For morphological analysis, 155 honeybee colony samples from 31 localities were collected. 20 worker honeybees per colony sample totalled 3100 individual worker honeybees and thirteen morphological characters per bee, a total of 40 300 measurements were recorded following Ruttner's (1988) protocols. The behavioural characters such as reproductive swarming, migration, temperament and colony seasonal cycles were assessed based on survey work of a pre-structured questionnaire. Various univariate and multivariate statistical methods were employed to analyse the data. The principal components and step-wise linear discriminant analyses revealed the existence of four discrete morphoclusters or geographical races: A. m. jemenitica from eastern, northwestern and northern arid and semi-arid lowlands, A. m. scutellata from the western humid midlands, A. m. bandasii from sub-moist central highlands and A. m. monticola from the northern mountainous parts of the study areas. These different geographical races were found to be distinctively distributed in the different ecological parts of the study area. High intercolonial and intracolonial variances were observed in all localities, however particularly high values were obtained in areas of transitions between ecological zones indicating a region of gene flow or zones of hybridisation among the statistically defined populations. Such high variances were observed mostly in areas where A. m. jemenitica borders the other geographical races. Moreover. distinct behavioural variations were also noted among these geographical races. Generally. the highland and mountainous honeybees A. m. bandasii and A. m. monticola are relatively larger in body size. have less tendency to swarm. less inclination to migrate and are relatively gentle while the converse traits were noted for the lowlands and midlands honeybees A. m. jemenitica and A. m. scutellata. Both morphological and behavioural variations were highly correlated with environmental factors and the variations seem to be the result of long adaptation to the interrelated ecological factors in their respective areas. Variations in reproductive swarming periods were also noted among these honeybee populations as a result of variations in rainfall pattern. altitude and temperature in their respective ecological areas which are believed to alter the honeybee colonies' seasonal cycles and leads to partial temporal reproductive isolation among these different honeybee populations.
Keywords: Honeybee -- Ethiopia; Honeybee -- Behavior -- Ethiopia; Honeybee -- Ethiopia -- Morphology; Honeybee -- Ecology -- Ethiopia